Development and Engineering of a Portable Vertical Wind Turbine for Lakefront Areas - Kurniawan, Ricky; Kusumanto, RD.; Carlos, R.S. (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Energy consumption is increasing daily and is heavily dependent on non-renewable energy sources, particularly petroleum, which is now dwindling in supply and becoming more costly to produce. There are numerous types of renewable energy that are plentiful, cost-effective, and environmentally friendly. To replace non-renewable fuels, the development of renewable energy must be prioritized. This research aims to prevent future energy shortages. By developing energy conversion devices, renewable energy can be optimally utilized in Indonesia to meet human energy needs. One such renewable energy source we encounter daily is wind energy. For instance, wind energy holds significant potential for use in lake regions. Lakefront areas frequently harness wind energy using windmills. The Savonius wind turbine, known for its ease of construction, is a practical windmill design. Its advantage lies in its ability to start rotating at low wind speeds.